(untitled) (Research, Society and Development, 2021)
The existence of faults, whether caused during exposure or in radiographic processing, results in inappropriate images that can interfere with the diagnosis and treatment of the patient. The purpose of this study is to provide information on the main types of errors made by dentistry students and the possible causes of these errors on periapical radiographs. It is a cross-sectional, observational study, with an inductive approach and a comparative, statistical and descriptive procedure. Data collection was performed based on the analysis of radiographs discarded by students due to radiographic errors that made their use unfeasible. The errors were categorized into radiographic technique errors and radiographic processing errors. In total, 114 radiographs were collected and analyzed by 3 dentists. The radiographic technique errors were the most found, corresponding to 81.58% of the total sample. The errors in radiographic processing were 18.42%. Among these, framing with tooth cuts was the most commonly found error (35.9%), followed by under-exposure (21.05%), over-exposure (14.04%) and vertical angle error (9.65%). In smaller percentages, partially revealed radiographs (6.14%), stained radiographs (5.26%), yellowish films (5.26%), appearance of a half moon (1.35%) and streaked (1.35%) were found ). It can be concluded that the main causes of these errors are the inadequate positioning of the patient and the X-ray apparatus, radiographs that have spent little or long time in contact with the processing solutions, improper handling of the film after processing, inappropriate storage, in addition to solutions with prolonged use time indicating chemical depletion.